Avaliação de um centro popular de compras abrigando antigos camelôs (ARQUISUR Revista, 2010)
This paper presents the evaluation of a shopping center built to house street vendors (CPC) in Porto Alegre, by shop owners (former street vendors) and users regarding the use, aesthetics and perception of security. The evaluation of the external appearance of the building is compared with the evaluation of architects. Still, the use of CPC by city center users is identified. The study is justified by the need for more knowledge regarding the impact of buildings used to accommodate street vendors. The methodology included archives surveys, physical measurements, behavioral observations, questionnaires and interviews. Data were analyzed by statistical non-parametric tests such as Kruskal-Wallis and Spearman. Although results indicate, for example, that users are more satisfied than shop owners, compared to the previous street vendors area in Praça XV the number of users decreased, mainly due to the difficulty in accessing the shops in CPC. Still, results show similar perception of security by shop owners and users, the bus terminal being perceived as unsafe by a significant part of respondents. Thus, this research contributes to knowledge about the impact caused by buildings with the physical characteristics and location such as the CPC, to different shop owners and users.
Keywords: post-occupancy evaluation; shopping center; former street vendors; urban space; environmental perception